Switch-Off Behaviour of 6.5 kV IGBT Modules in Two-Level Voltage Source Inverter - Blinov, Andrei; Jalakas, Tanel; Vinnikov, Dmitri; Janson, Kuno (Electrical, Control and Communication Engineering, 2010)
This paper presents an analysis of the switch-off process of 6.5 kV/200 A IGBT modules in a two-level half-bridge voltage source inverter. During experiments, it was stated that real switching process is far from ideal switch-off since parasitic inductance and capacitance in the circuit cause voltage spikes and high frequency oscillations during transition processes. Operation states of the inverter are described and analyzed. Experimental and simulation results are compared, the main transients are analyzed and mathematically expressed and possible problems and solutions are discussed.